Simultaneous linearization of a class of pairs of involutions with normally hyperbolic composition - Mancini, Solange [UNESP]; Manoel, Miriam; Teixeira, Marco Antonio (Elsevier, 2013)
In this paper we obtain a result on simultaneous linearization for a class of pairs of involutions whose composition is normally hyperbolic. This extends the corresponding result when the composition of the involutions is a hyperbolic germ of diffeomorphism. Inside the class of pairs with normally hyperbolic composition, we obtain a characterization theorem for the composition to be hyperbolic. In addition, related to the class of interest, we present the classification of pairs of linear involutions via linear conjugacy. © 2012 Elsevier Masson SAS.
Keywords: Involution; Linearization; Normal hyperbolicity; Transversality